A Case Study of Analysis of Natural Frequency Variability Related to Manufacturing Process - T. Uhl; W. Lisowski (Shock and Vibration)
One of the important challenges present nowadays in the automotive industry is minimizing of a car components design time. Traditional manufacturing of a prototype is usually a time and a cost consuming process. Alternatively, rapid prototyping techniques can be used in such a case. In the reported research a brake caliper was investigated, since it is an example of an element, which should have very strictly defined structural dynamic properties. As a technique of rapid prototyping of the considered caliper the 3D printing of a mould was selected. A process of the caliper casting with the use of the "prototype" mould is different than the one with the use of the metal form. Thus it is very likely that the both considered types of the caliper would possess different properties from the point of view of structural dynamics.